Disruption of a microvitellogenin gene impairs eggshell formation in Mythimna separata - Lingling Li; Junhong Fu; Changgeng Dai; Yuhang Zhou; Yang Hu; Hongbo Li (Journal of Integrative Agriculture, 2024)
Microvitellogenin (mVg) belongs to the lepidopteran-specific lipoprotein_11 super family and is thought to be involved in insect reproduction. However, the function of mVg in reproduction has not been established. In this study, we identified and characterized MsmVg in Mythimna separata, a destructive insect pest of grain crops. MsmVg is comprised of a 1,310 bp open reading frame (ORF) encoding 437 amino acids. Structural analysis showed that MsmVg contains three conserved domains in the lipoprotein_11 super family, including the all-α-N-terminal domain (NTD), a Pseudomonas putida homologous domain (PPD), and an all-β-C-terminal domain (CTD). MsmVg was highly expressed in mature female adults and enriched in the ovaries of 3-day-old female adults. Disruption of MsmVg by RNA interference did not change the expression of MsmVg, vitellogenin (MsVg) or the vitellogenin receptor (MsVgR) in fat bodies, but it inhibited their transcription in ovaries. Phenotype analysis showed that knockdown of MsmVg did not affect yolk deposition in ovaries, but impaired eggshell formation and led to a reduction in the reproductive capacity. Furthermore, knockdown of MsmVg significantly inhibited the expression of genes associated with eggshell formation (MsChP1-3 and MsFcP3C). Taken together, these data suggest that MsmVg plays an important role in female reproduction by affecting eggshell formation in M. separata, which provides a potential target for managing this insect pest.